Validity and reliability of measurements of aponeurosis dimensions from magnetic resonance images. (4th March 2019) - Bird, Lachlan; D'Souza, Arkiev; Ball, Iain; Rae, Caroline; Herbert, Robert D.; Bolsterlee, Bart
Abstract : Muscle performance is closely related to the structure and function of tendons and aponeuroses, the sheet‐like, intramuscular parts of tendons. The architecture of aponeuroses has been difficult to study with magnetic resonance imaging (MRI) because these thin, collagen‐rich connective tissues have very short transverse relaxation (T2) times and therefore provide a weak signal with conventional MRI sequences. Here, we validated measurements of aponeurosis dimensions from two MRI sequences commonly used in muscle‐tendon research (mDixon and T1‐weighted images), and an ultrashort echo time (UTE) sequence designed for imaging tissues with short T2 times. MRI‐based measurements of aponeurosis width, length, and area of 20 sheep leg muscles were compared to direct measurements made with three‐dimensional (3D) quantitative microdissection. The errors in measurement of aponeurosis width relative to the mean width were 1.8% for UTE, 3.7% for T1, and 18.8% for mDixon. For aponeurosis length, the errors were 7.6% for UTE, 1.9% for T1, and 21.0% for mDixon. Measurements from T1 and UTE scans were unbiased, but mDixon scans systematically underestimated widths, lengths, and areas of the aponeuroses. Using the same methods, we then found high inter‐rater reliability (intraclass correlation coefficients >0.92 for all measures) of measurements of the dimensions of the central aponeurosis of the human tibialis anterior muscle from T1‐weighted scans. We conclude that valid and reliable measurements of aponeurosis dimensions can be obtained from UTE and from T1‐weighted scans. When the goal is to study the macroscopic architecture of aponeuroses, UTE does not hold an advantage over T1‐weighted imaging.